A Blood Bank Standardized Production of Human Platelet Lysate for Mesenchymal Stromal Cell Expansion: Proteomic Characterization and Biological Effects - Bianchetti, Andrea; Chinello, Clizia; Guindani, Michele; Braga, Simona; Neva, Arabella; Verardi, Rosanna; Piovani, Giovanna; Pagani, Lisa; Lisignoli, Gina; Magni, Fulvio; Russo, Domenico; Almici, Camillo (Frontiers in Cell and Developmental Biology, 2021)
Human Platelet Lysate (hPL) is considered a valid substitute to foetal bovine serum (FBS) in mesenchymal stromal cells (MSC) expansion and it is commonly produced starting from intermediate side-products of whole blood donations. Through freeze-thaw cycles, hPL is highly enriched in chemokines, growth factors and adhesion and immunologic molecules. Cell therapy protocols, using hPL instead of FBS for cells’ expansion, are approved by regulatory authorities without concerns and administration in patients is considered safe. However, published data are fairly difficult to compare, since the production of hPL is highly variable. This study proposes to optimize and standardize the hPL productive process by using instruments, technologies and quality/safety standards required for Blood Banks activities and products. The quality and improved selection of the starting material (i.e. the whole blood), together with the improvement of the production process, guarantee a product characterized by higher content and quality of growth factors as well as a reduction in batches’ variability. By increasing the number of freeze/thaw cycles from one (hPL1c) to four (hPL4c), we obtained a favourable effect on the release of growth factors from platelet  granules. Those changes have directly translated into biological effects leading to a decreasing Doubling Time (DT) of MSC expansion at 7 days (49.41±2.62 hours vs 40.61±1.11 hours, P<0.001). Furthermore, Mass Spectrometry (MS)-based evaluation has shown that the proliferative effects of hPL4c are also combined with a lower batch-to-batch variability (10-15% vs 21-31%) at the proteomic level. In conclusion, we have considered lot-to-lot hPL variability and, by the strict application of Blood Bank standards, we have obtained a standardized, reproducible, safe, cheap and ready-to-use product.